Educação especial e condições de acessibilidade em instituições de ensino superior público e privado - Okubo, Vera Lúcia Luvizutto (2017)
The inclusion of disabled students, as a consequence of a quality education for everyone, requires a new position from public and private education, which is a new reason for teachers; pedagogical coordinators and education people improve their knowledge. It is an innovation that implies in an effort to update and restructure the actual teaching conditions. The fight for inclusion is the guarantee that everyone will have access to learning in all areas, levels and degrees, and it has to be offered with special requirements and accessibility. This research aimed to investigate how many students with specific needs are fairly enrolled and collect information about accessibility conditions. Five college institutions were surveyed at Bauru, SP, two privates and three publics. People who are part from academic boards and coordinators answered a form to determine accessibility conditions and a semi-structured interview to quantify the amount of students with specific needs. It was verified that the responsible committees, along with managers, are making an effort to make accessibility more possible in many ways, but full compliance with the standards keeps happening gradually with the objective of eliminate any problems those students can have. This study showed that the number of students with specific needs is still not significant. Moreover, it was verified the need of bigger investments of colleges in accessibility actions in order to guarantee access to students with any specific needs